2008
DOI: 10.1007/s00122-008-0923-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of chickpea EST-SSR markers and analysis of allelic variation across related species

Abstract: Despite chickpea being the third important grain legume, there is a limited availability of genomic resources, especially of the expressed sequence tag (EST)-based markers. In this study, we generated 822 chickpea ESTs from immature seeds as well as exploited 1,309 ESTs from the chickpea database, thus utilizing a total of 2,131 EST sequences for development of functional EST-SSR markers. Two hundred and forty-six simple sequence repeat (SSR) motifs were identified from which 183 primer pairs were designed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
122
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 50 publications
18
122
5
2
Order By: Relevance
“…The SSR markers from Medicago truncatula exhibited transferability to faba bean, chickpea, and pea (Gutierrez et al, 2005). The EST-SSR markers from chickpea also showed high transferability to the six Cicer species and seven legume genera (P. mungo, P. sativum, G. max, T. alexandrinum, L. esculenta, C. cajan, and M. truncatula) (Choudhary et al, 2009). The present results show that three loci of nine polymorphic P. sativum EST-SSR markers can be amplified in faba bean, which suggests that it may assist in reducing the costs of marker development, and promote genetic analysis among the bean species.…”
Section: Discussionmentioning
confidence: 93%
“…The SSR markers from Medicago truncatula exhibited transferability to faba bean, chickpea, and pea (Gutierrez et al, 2005). The EST-SSR markers from chickpea also showed high transferability to the six Cicer species and seven legume genera (P. mungo, P. sativum, G. max, T. alexandrinum, L. esculenta, C. cajan, and M. truncatula) (Choudhary et al, 2009). The present results show that three loci of nine polymorphic P. sativum EST-SSR markers can be amplified in faba bean, which suggests that it may assist in reducing the costs of marker development, and promote genetic analysis among the bean species.…”
Section: Discussionmentioning
confidence: 93%
“…Despite its importance in nutritional security, pigeonpea has not benefited much from the advances made in the field of genomic tools and molecular markers (Datta et al, 2009). As compared to large number of markers in common bean (L'taief et al, 2008;Blair et al, 2003), chickpea (Choudhary et al, 2009;Sethy et al, 2006), and lentil (Hamwieh et al, 2009;Hamwieh et al, 2005), only 109 microsatellite markers are reported so far in pigeonpea (Burns et al, 2001;Odeny et al, 2007;Odeny et al, 2009). Therefore, there is an urgent need to increase the number of polymorphic microsatellite markers in pigeonpea for diversity analysis and mapping of important traits.…”
Section: Introductionmentioning
confidence: 99%
“…The neighbor joining dendrogram clearly separated the chickpea cultivars from the wild Cicer and validated the proximity of C. judaicum Choudhary et al, 2009 10 SSR markers 47 chickpea (C. arietinum) accessions including 21 induced mutation lines, 17 hybrid lines, 5 local cultigens, and 4 non-nodulating lines UPGMA and ME (minimum evolution) trees classified the accessions into 6 groups and all but 6 accessions could be clearly separated.…”
Section: Upadhyaya Et Al 2008mentioning
confidence: 54%